MEDIASI PENYELESAIAN KONFLIK PENDIRIAN RUMAH IBADAH (STUDI KASUS PENOLAKAN PENDIRIAN GEREJA BAPTIS INDONESIA DI KELURAHAN TLOGOSARI KULON SEMARANG) - Dizafia Zafira Mayyasya; Turnomo Rahardjo; Triyono Lukmantoro (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2022)
Indonesia is a country where there is a lot of diversity that has the principle of Bhineka Tunggal Ika, but Indonesia cannot be separated from conflicts related to diversity. Semarang as one of the cities in Indonesia is a city with a multicultural society due to the diversity of tribes, races, nations and religions and backgrounds. In Semarang, the most common diversity conflicts are conflicts based on religion, one of which is the case of the establishment of the Indonesian Baptist Church (GBI) Tlogosari Kulon Semarang. On this basis, the author is interested in analyzing and describing the picture of the conflict and the negotiation process in resolving the conflict to establish a house of worship for the Indonesian Baptist Church (GBI) Tlogosari Kulon Semarang. This study aims to explain the description of the conflict and the negotiation process for the construction of GBI Tlogosari Kulon Semarang. This research was conducted with a descriptive method through a qualitative approach with a single case study. The research sample was selected by purposive sampling method, including the Sematang City Spatial Planning Service, Tlogosari Kulon Village Office, Pendurungan District Office, GBI Tlogosari Kulon, Forum Kerukunan Umat Beragama (FKUB) Of Semarang City, and the surrounding community. The research data will be analyzed using Conflict Management Theory, Conflict Resolution Theory, Face Negotiation Theory, Conflict Theory, and Ethnocentrism Concepts that are used to explain the description of the occurrence of conflict and the mediation process for the development of GBI Tlogosari Kulon Semarang. The results showed that the conflict occurred because the signature letter given to the residents with the reason for the residents' thanksgiving event was in fact used as a church construction permit, an expired IMB, and there are no Malangsari residents who participate in using the place of worship. There was never any negotiation that took place between the two parties and this final settlement used the mediation process. It is recorded that 6 times mediation has been carried out. The mediators involved were the FKUB Of Semarang City and KOMNAS HAM. Conflict management that occurred in the case of the construction of the Indonesian Baptist Church (GBI) is constructive conflict management